Bevacizumab plus XELOX as first-line treatment of metastatic colorectal cancer: The OBELIX study - Antonuzzo, Lorenzo (World J Gastroenterol, 2015)
AIM: To confirm the efficacy and safety of bevacizumab/XELOX combination for the treatment of locally advanced or metastatic colorectal cancer (CRC) in Italy. METHODS: This multicentric, prospective, open-label study included patients with CRC previously untreated with chemotherapy. Patients were administered bevacizumab in combination with XELOX. The primary efficacy end-point was progression-free survival (PFS). Secondary end-points included time to overall response (TOR), duration of response (DOR), time to treatment failure (TTF) and overall survival (OS). The incidence and type of adverse events AEs and severe AEs were evaluated. Also, the mutational status of BRAF and KRAS was assessed by high resolution melting and direct sequencing, and quality of life (QoL) was measured by the EuroQoL EQ-5D questionnaire at baseline and at the last visit. RESULTS: The intention-to-treat population included 197 patients (mean age: 62.3 ± 9.9 years, 56.4% males). At baseline, 16/34 evaluable subjects (47.1%) harbored a KRAS and/or a BRAF mutation; the mean QoL index was 80.2 ± 14.3. First-line therapy was given for 223.7 ± 175.9 d, and after a mean follow-up of 387.7 ± 238.8 d all patients discontinued from the study mainly for disease progression (PD, 45.4%) and AEs (25.4%). Median PFS was 9.7 mo (95%CI: 8.4-10.5) and the median values for secondary end-points were: TOR = 3.9 mo (95%CI: 2.6-4.7), DOR = 8.5 mo (95%CI: 7.3-10.3), TTF = 6.7 mo (95%CI: 6.0-7.7) and OS = 23.2 mo (95%CI: 20.1-27.2). Patients carrying at least one lesion had a lower overall response rate (66.7% vs 88.9%) and a lower probability of achieving complete or partial response than those without mutations, but the difference in relative risk was not statistically significant (P = 0.2). Mean EQ-5D-3L raw index score significantly decreased to 74.9 ± 19.1 at the last visit (signed-rank test, P = 0.0076), but in general the evaluation on QoL perceived by patients was good. CONCLUSION: The efficacy of bevacizumab in combination with XELOX in terms of PFS in patients with aCRC or mCRC in Italy was confirmed, with acceptable toxicity.